2008
DOI: 10.1158/1078-0432.ccr-07-1806
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Proteomics Analyses of OSU03013 in Lung Cancer

Abstract: Purpose: Most lung cancer patients have some resistance to and suffer from side effects of conventional chemotherapy. Thus, identification of a novel anticancer drug with better target selectivity for lung cancer treatment is urgently needed. Experimental Design: In order to investigate whether OSU03013, a derivative of celecoxib, can be a potential drug for lung cancer treatment, we examined its cytotoxicity mechanisms by flow cytometry and phosphatidylserine staining in A549, CL1-1, and H1435 lung cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…It has been reported that ANXA3 could promote angiogenesis, possibly through stimulating VEGF and bFGF production, suggesting that ANXA3 might play critical roles in cancer metastasis via promoting angiogenesis 50. Recent studies have also shown that: (a) ANXA3 is necessary for DNA replication in cultured hepatocytes 51; ANXA3 abundance is increased in approximately two‐thirds of colorectal tumours 52; ANXA3 is down‐regulated in prostate cancer cells and an independent adverse prognostic factor 53; and OSU03 013, a derivative of celecoxib, exhibits its antitumour activity by decreasing ANXA3 expression in A549, CL1‐1 and H1435 lung cancer cell lines 54. Our results, together with previous reports, strongly suggest that ANXA3 might serve as a novel biomarker for lymph node metastasis and prognosis in lung AdC, and play an important role in lung AdC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ANXA3 could promote angiogenesis, possibly through stimulating VEGF and bFGF production, suggesting that ANXA3 might play critical roles in cancer metastasis via promoting angiogenesis 50. Recent studies have also shown that: (a) ANXA3 is necessary for DNA replication in cultured hepatocytes 51; ANXA3 abundance is increased in approximately two‐thirds of colorectal tumours 52; ANXA3 is down‐regulated in prostate cancer cells and an independent adverse prognostic factor 53; and OSU03 013, a derivative of celecoxib, exhibits its antitumour activity by decreasing ANXA3 expression in A549, CL1‐1 and H1435 lung cancer cell lines 54. Our results, together with previous reports, strongly suggest that ANXA3 might serve as a novel biomarker for lymph node metastasis and prognosis in lung AdC, and play an important role in lung AdC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several comprehensive proteomic analyses of cancer cells treated with celecoxib have been studied in lung can- cer, oral squamous cell carcinoma and colorectal carcinoma [22]- [24]. Another study used cardiomyocytes to investigate the cardiovascular toxicity of NSAIDs including celecoxib [25].…”
Section: Discussionmentioning
confidence: 99%
“…The K562 cells were differentiated into K562 basophilic-EB-like cells using 30  μ M haemin, and the monocytic THP-1 cells were differentiated into THP-1 macrophage-like cells using 160 nM phorbol-12-myristate-13-acetate (PMA) (Sigma) [21]. To select for apoptosis-resistant clones (EGFP-ANXA3 K562 R cells) using limiting dilution methods, the EGFP-ANXA3 K562 cells were cultured for 3 days in the presence of 1 mM MnCl 2 [18, 22]. To examine the haemin-induced differentiation of the K562 cells using fluorescence-activated cell sorting (FACS), the cells were stained with FITC-conjugated anti-CD71 and PE-conjugated anti-CD235a mouse IgGs for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%